Kondisi Burnout Akademik Pada Siswa Indonesia: Fisik, Mental, Dan Emosional - Agus Supriyanto; Salsabila Imtinan; Suharsimi Arikunto; Sri Hartini (Universitas Veteran Bangun Nusantara, 2022)
The unclear end of the Covid-19 pandemic impacts learning in schools. Students as affected communities lead to an online learning process with various limitations, even though students are already getting used to online learning. Conditions related to online learning raise new problems regarding academic burnout. This study aims to develop an academic burnout scale and describe the situation of students' academic burnout. The research method uses a mix-method with academic burnout variables, and the target is students. The study results found three aspects of academic burnout conditions physical exhaustion, mental exhaustion, and emotional exhaustion. Tested the burnout scale for validity with reliability in the very high category. The measurement of students' academic burnout found that, on average, students had a high burnout category due to online learning. The effect of the burnout condition is self-confidence, motivation, achievement, self-control or depression in students. Immediate intervention for the prevention, reduction, or alleviation of burnout by a school counsellor or collaboration with a psychologist or university.